Pengaruh Variasi Ketebalan Komposit Serat Kelapa terhadap Koefisien Absorpsi Bunyi pada Frekuensi Rendah - Raihan Arsy Wildani Hidayat; Rizal Hanifi; Aa Santosa (Yayasan Literasi Sains Indonesia, 2025)
This study aims to investigate the effect of coconut fiber composite thickness on the sound absorption coefficient using a two-microphone impedance tube. The composites were fabricated with thickness variations of 1 cm and 2 cm using the hand lay-up method, with polyester resin as the matrix and coconut fiber as the reinforcement. The tests were conducted at frequencies of 400 Hz, 450 Hz, and 500 Hz. Data processing was carried out using LabVIEW and MATLAB software. The results show that the composite with a thickness of 2 cm exhibited a higher sound absorption coefficient compared to the 1 cm thickness across all tested frequencies. The highest sound absorption coefficient was recorded at 0.175 at 400 Hz for the 2 cm thickness. However, the absorption capability significantly decreased at higher frequencies, particularly for the 1 cm thickness, which showed no absorption at 500 Hz. These findings indicate that coconut fiber has potential as an environmentally friendly sound-absorbing material, especially in the low-frequency range.